Pancreaticoduodenectomy with venous reconstruction using cold‐stored vein allografts: long‐term results of a single center experience. (10th December 2015) - Meniconi, Roberto L.; Santoro, Roberto; Guglielmo, Nicola; Vennarecci, Giovanni; Lepiane, Pasquale; Colasanti, Marco; Ettorre, Giuseppe M.
Abstract: Background: The use of cadaveric vein allografts was first described by our group as a feasible option for venous reconstruction. The aim of this study was to report long‐term results of this innovative technique. Methods: Cold‐stored veins harvested from donor cadavers were used as homologous grafts for venous reconstruction after vascular resection during pancreaticoduodenectomy. Surgical technique included patch closure or segmental interposition. Graft patency was assessed by computed tomography postoperatively and during follow‐up. Postoperative morbidity and mortality were also analyzed. Results: Eleven patients underwent venous resection and reconstruction by using fresh vein allografts for patch closure in four cases, conduit interposition in six cases and a Y‐shaped graft interposition in one case. Median clamping time, operative time and estimated blood loss were 30 min, 6.6 h, and 337 ml, respectively. One patient, who had preoperative SMV thrombus, developed early portal vein thrombosis and died. Among the remaining 10 patients, there were no cases of graft thrombosis or stenosis during active follow‐up (median 9, range 1–23, months). Conclusions: Our experience with cold‐stored vein allografts suggests that this technique is a useful option for treating major vascular resections during pancreaticoduodenectomy with good results on follow‐up. Abstract : Highlight Meniconi and colleagues evaluated the technical feasibility and efficacy of cold‐stored vein allografts used as patches or conduits for venous reconstruction during pancreaticoduodenectomy. This innovative technique was confirmed to be a safe and effective treatment option, particularly for segmental reconstructions longer than 4 cm, providing good results on long‐term follow‐up.